Reliability and Validity of the Turkish Adaptation of VITACORA-19 in Patients with Psoriatic Arthritis - Berna TANDER,; Yasemin ULUS,; Yüksel TERZİ,; Yeliz ZAHİROĞLU,; Hakan KESMEN,; Bayram FARİSOĞULLARI,; Yeşim AKYOL,; Ayhan BİLGİCİ,; Ömer KURU, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate the reliability and validity of the Turkish language version of VITACORA-19 (psoriatic arthritis quality of life questionnaire) in patients with psoriatic arthritis. Patients and methods: The Turkish version of VITACORA-19 questionnaire was obtained after a translation and back translation process. The study sample included 61 PsA patients (22 males, 39 females; mean age 46.5±12.2 years; range 19 to 71 years). To assess the test-retest reliability of the Turkish VITACORA-19, the questionnaire was reapplied 10 to 15 days after the first interview (interclass correlation coefficient). Cronbach’s alpha (a) was used to evaluate the internal consistency. VITACORA-19 was compared with visual analog scale for physician and patient global assessments, the Health Assessment Questionnaire, and Nottingham Health Profile for construct validity. The internal structure of VITACORA-19 was examined by factor analysis. Results: The individual item intraclass correlation coefficient ranged from 0.77 to 0.98 and Cronbach's alpha ranged from 0.77 to 0.98. The Cronbach's alpha value for whole scale was determined as 0.96. The Kaiser-Meyer-Olkin measure of sampling adequacy was 0.90, and Bartlett's test of sphericity had a p<0.001. Turkish VITACORA-19 total scores were correlated negatively with Health Assessment Questionnaire, visual analog scale for pain, and Nottingham Health Profile subgroups, and positively with physician and patient global assessments (p<0.01). Conclusion: Turkish version of VITACORA-19 questionnaire is a reliable and valid measure for health-related quality of life in Turkish patients with psoriatic arthritis.